PENGARUH PERBEDAAN KONSENTRASI GEL OKRA HIJAU DAN KARAGENAN TERHADAP KARAKTERISTIK JELLY DRINK OKRA HIJAU (Abelmoschus Esculentus L.) - Rosyada, Amrina; Masahid, Ardiyan Dwi; Brihatsama; Priyantono, Eko (Jurnal Penelitian Sains dan Teknologi Indonesia, 2025)
The potential of green okra lies in its high dietary fiber component. Efforts to utilize dietary fiber in green okra include processing it into jelly drink product. The aim of this is to determine the influence of adding concentrations of green okra gel and carrageenan on the physical, chemical and organoleptic properties, as well as to determine the appropriate formulation of different concentrations of green okra gel and carrageenan to produce jelly drink green okra with the best physical, chemical and organoleptic properties. The experimental design used was a factorial completely randomized design (CRD) consisting of green okra gel concentrations (A) of 15%, 30%, 45%, 60%, and carrageenan concentrations (B) of 0.30% and 0.40%. The observational data were analyzed using ANOVA followed by DMRT test. Based on the research results, it can be concluded that the differences in green okra gel concentration and carrageenan concentration significantly affect the a* (redness), b* (yellowness), total solids, syneresis, pH, color liking score, aroma, taste, texture, and overall liking. The effectiveness values indicate that the best-treated green okra jelly drink has a pH value of 3.42, syneresis of 30.12%, total solids content of 14.17%, and dietary fiber content of 0.81%. In the organoleptic test, color liking score was 6.68 (like), taste 6.0 (like), aroma 5.64 (somewhat like), texture 5.48 (somewhat like), and overall liking 6.16 (like).